The Use of Scanning Electron Microscope in Forensic Sciences - Büken, Bora; Üner, Hüseyin Bülent; Çetinkaya, Ümit; Çağdır, Ahmet Sadi; Kırangil, Şerife Bilge (The Bulletin of Legal Medicine, 2001)
As in many fields of science and technology, with advancing technology some new investigation methods in forensic sciences have come in to use and by using these techniques "the concepts of crime and offender" have begun to be assessed in the context of evidence. One of the advanced tecniques used in the investigation of evidence is the electron microscopy. In this article, after mentioning the electron microscope briefly, studies that can be performed by the electron microscope are presented. The authors have mentioned the electron microscope facilities that can be used for the investigation of forensic cases.Key Words: Scanning electron microscope, forensic sciences, x-ray analysis.
Keywords: scanning electron microscope; forensic sciences; x-ray analysis